Determinants of market participation decision and intensity of market participation in western Ethiopia: Evidence from smallholder tef producers - Kifle Degefa; Galmesa Abebe; Getachew Biru (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2022)
Tef is the first crop produced in Ethiopia and the main staple food and income generation source. The productivity of the crop is low due to different factors. This study aimed to identify factors affecting tef market participation decision and the level of market participation of tef producers'. Multi-stage sampling techniques were used to select appropriate sample households. The descriptive statistic, inferential statistic, and econometrics model were used to analyze the collected data. The result shows that 72.27% of sampled households sold their tef in the market. The double hurdle model result revealed that tef market participation decision was affected by land allocated for tef, the volume of tef produced, gender of household head, education level of household head, additional income sources, extension services, and market information while the intensity of participation was affected by the volume of tef produced, gender, education level, improved variety used, additional income sources, and extension service. These results suggest that to enhance the flow of tef to market and intensity of tef in participation skills and knowledge through training, advising, and supervision; capacitate farmers by the additional work atmosphere and empowering women farmers through improved variety and to access working capital are need attention by respective sectors that contribute in the commodity value chain.